Transient Global Amnesia (TGA): Younger Age and Absence of Cerebral Microangiopathy Are Potentially Predisposing Factors for TGA Recurrence - Rogalewski, Andreas; Beyer, Anne; Friedrich, Anja; Plümer, Jorge; Zuhorn, Frédéric; Klingebiel, Randolf; Woermann, Friedrich G.; Bien, Christian G.; Greeve, Isabell; Schäbitz, Wolf-Rüdiger (Frontiers in Neurology, 2021)
Background: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear aetiology for a period of less than 24 hours. TGA occurs as a single event in most cases. Prevalence rates of recurrent TGA vary widely from 5.4% to 27.1%. This retrospective study aimed to determine predictors for TGA recurrence. Methods: Cardiovascular risk profile and magnetic resonance imaging (MRI) of 340 hospitalized TGA patients between 2011 and 2020 were retrospectively analysed. The median follow-up period amounted to 4.5±2.7 years. Comparisons were made between TGA patients with and without subsequent recurrence. Results: TGA patients with subsequent recurrence were significantly younger (recurrent vs. single episode, 63.6±8.6 years vs. 67.3±10.5 years, p=0.032) and showed a lower degree of cerebral microangiopathy compared to TGA-patients without recurrence. The mean latency to recurrence was 3.0 years±2.1 years after the first episode. In a subgroup analysis, patients with at least five years of follow-up (N=160, median follow-up period 7.0±1.4 years) had a recurrence rate of 11.3%. A 24.5% risk of subsequent TGA recurrence in the following five years was determined for TGA patients up to 70 years of age without microangiopathic changes on MRI (Fazekas’ score 0). Conclusions: Younger TGA patients without significant microangiopathy do have an increased recurrence risk. In turn, preexisting cerebrovascular pathology, in form of chronic hypertension and cerebral microangiopathy, seem to counteract TGA recurrence.